1998
DOI: 10.1002/(sici)1097-0142(19980101)82:1<86::aid-cncr10>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the expression of p53, MIB-1 (Ki-67 antigen), and argyrophilic nucleolar organizer regions in carcinoma of the extrahepatic bile duct

Abstract: MIB-1, and the argyrophilic nucleolar organizer regions (AgNOR) and examined the relationships among them in carcinoma of the extrahepatic bile duct (EHBD). Shin-ichi RESULTS. MIB-1 and AgNOR were closely associated with lymph node metastasisIwate Medical University, Morioka, Japan.(P õ 0.01). The cumulative survival rate for patients with a low MIB-1 labeling index (LI) (õ29%) was significantly better than that for patients with a high MIB-2 Division of Pathology, Central Clinical Laboratory, School of Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 34 publications
3
34
0
1
Order By: Relevance
“…There was no invasive growth microscopically, but positive immunoreactivity for MIB-1 and p53 suggested the malignant potential of the lesion. Suto et al 27 reported that alterations of p53 may be a rather early event in the progression of extrahepatic biliary carcinoma, because accumulation of changes is observed in early cancer without metastasis. Finally, we diagnosed this lesion as a papillary adenoma with focal severe atypia.…”
Section: Discussionmentioning
confidence: 99%
“…There was no invasive growth microscopically, but positive immunoreactivity for MIB-1 and p53 suggested the malignant potential of the lesion. Suto et al 27 reported that alterations of p53 may be a rather early event in the progression of extrahepatic biliary carcinoma, because accumulation of changes is observed in early cancer without metastasis. Finally, we diagnosed this lesion as a papillary adenoma with focal severe atypia.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, according to the inclusion and exclusion criteria, there were ten eligible studies published from 1994 to 2006. There were two studies, both reported by Suto et al, based on the same patient cohort [15,24]. So we gave up the study whose number of patients is smaller [24].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Two studies were excluded because we could not extract the data of p53 and its impact on survival [25,26]. Finally, a total of seven independent studies were included in this meta-analysis [11][12][13][14][15][16][17].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations